Sexual violence in medical students and specialty registrars in Flanders, Belgium: a population survey - Geldolf, M. (BMC Med Educ, 2021)
BACKGROUND: Sexual violence has globally been recognized as harmful to young people’s health. In medical school, which is a highly competitive environment, the risk is supposedly even bigger. In this study we firstly aimed to investigate the magnitude and precipitating factors of sexual violence in medical students and specialty registrars in Flanders, Belgium. Secondly, we wanted to assess the reactive behaviours as well as the knowledge of possible types of bystander reactions as well as potential support resources for victims of sexual violence. METHODS: This study was initiated and coordinated by the Flemish medical student representation organisation (VGSO). A survey containing demographic and behaviour-specific questions based on the UNMENAMAIS and SAS-V questionnaire was sent to all undergraduate, graduate and postgraduate students of the 5 medical schools in Flanders. Participants were asked to limit their responses to internship-related events. Further questions concerning reactions to sexual violence, assailants, bystander reactions and general knowledge concerning support after sexual violence were asked. RESULTS: We received 3015 valid responses to our survey, obtaining a response rate of 29% in the potential target population. Within the total study population, 1168 of 3015 participants (38,73%) reported having been victim of at least one type of sexual violence as explored by our survey. This percentage was the highest in GP specialty registrars (53%), followed by specialty registrars (50%) and master students (39%). Assailants of sexual violence varied, most often they were medical staff members, students or patients. In most types of sexual violence, nobody reacted to this behaviour. Women (57.3%) talked about what happened afterwards more often than men (39.7%). When asked about their knowledge of possible bystander reactions and support services for sexual violence, 60% of the respondents did not know about their existence. CONCLUSIONS: Sexual violence is still a relatively frequent issue in medical students and specialty registrars. Patients form an important part of the assailants. In a third of reported sexual violence cases, nobody reacted. In addition, male victims seem to underreport. There is still much need for sensitisation on support mechanisms and centres for victims and witnesses of sexual violence.